(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
This research examines the National Nature Restoration Plan (NRP), introduced by Regulation (EU) 2024/1991, as an innovative tool for environmental and climate governance. The Plan marks a significant shift in European policies, defining a binding framework for ecosystem restoration based on measurable objectives and a pre-established timeline. The analysis goes beyond the regulatory aspect, considering the NRP as a testing ground for new decision-making models based on scientific knowledge, interinstitutional coordination, and social participation. The paper delves into the legal framework, administrative challenges, and the potential for multilevel integration, with a focus on transparency, democratic legitimacy, and policy effectiveness.